KONTROL DIRI, DUKUNGAN SOSIAL TEMAN SEBAYA DAN PROKRASTINASI AKADEMIK PADA MAHASISWA TINGKAT AKHIR - Rizky Septyan Rachmawan; Dewi Mahastuti; Andi Maulida Rahmania (Fakultas Psikologi Universitas Hang Tuah, 2021)
This study aims to determine the relationship between self-control and peer social support with academic procrastination independently and simultaneously. The research respondents were 56 final year students, selected using a saturated sampling technique. The scales in this research are self-control, peer social support and academic procrastination scale. The results showed a significant relationship between the variables of self-control and peer social support with academic procrastination. Other results show that self-control and social support have a negative correlation with academic procrastination in final year students.